Given:
Required:
We need to find the first differences, second differences, and first difference ratios.
Step-by-step explanation:
Recall that the first difference is the difference between values of the dependent variable by subtracting the previous value from each.
![(1)/(9)-(1)/(27)=(1*3)/(9*3)-(1)/(27)=(3)/(27)-(1)/(27)=(2)/(27)](https://img.qammunity.org/2023/formulas/mathematics/college/e7jluwfg3tkm0oju27bv2j23wy1ic6y9uu.png)
![(1)/(3)-(1)/(9)=(1*3)/(3*3)-(1)/(9)=(3)/(9)-(1)/(9)=(2)/(9)](https://img.qammunity.org/2023/formulas/mathematics/college/lo4vfbra5d5azqtifv31868f6p7eh2jtz2.png)
![1-(1)/(3)=(1*3)/(1*3)-(1)/(3)=(3)/(3)-(1)/(3)=(2)/(3)](https://img.qammunity.org/2023/formulas/mathematics/college/veen1cbv4h3nju8nim5bgeifjar9cwko6i.png)
![3-1=2](https://img.qammunity.org/2023/formulas/mathematics/high-school/3xqccinyrbpcqw2wcllkqfsguhfm38p3nn.png)
![9-3=6](https://img.qammunity.org/2023/formulas/mathematics/college/x96pu29461uxhvq2ag8cjdw2lh8lc5id38.png)
Recall that the second difference is the difference of the first difference.
![(2)/(9)-(2)/(27)=(2*3)/(9*3)-(2)/(27)=(6)/(27)-(2)/(27)=(4)/(27)](https://img.qammunity.org/2023/formulas/mathematics/college/exs4nw61fi856xbhzj3rmtmfakm9nxr5kn.png)
![(2)/(3)-(2)/(9)=(2*3)/(3*3)-(2)/(9)=(6)/(9)-(2)/(9)=(4)/(9)](https://img.qammunity.org/2023/formulas/mathematics/college/97099ey3ooqk6vxdwavatdka67bjc8pzd7.png)
![2-(2)/(3)=(2*3)/(1*3)-(2)/(3)=(6)/(3)-(2)/(3)=(4)/(3)](https://img.qammunity.org/2023/formulas/mathematics/college/f9vmwxr5cdmb2e120zvz5gchcuo1bje1me.png)
![6-2=4](https://img.qammunity.org/2023/formulas/mathematics/college/yew0iun1u4wua4vjyhfj2s03z6flqu8h59.png)
Divide the second number by the first number to find the ratio of the two numbers in the first difference.
![(2\/9)/(2\/27)=(2)/(9)*(27)/(2)=3](https://img.qammunity.org/2023/formulas/mathematics/college/owmpld66qqsze0wjgpz0q063ffiv16h2hh.png)
![(2\/3)/(2\/9)=(2)/(3)*(9)/(2)=3](https://img.qammunity.org/2023/formulas/mathematics/college/klru851iejswyliwuhoz8pib8thpj4kekv.png)
![(2)/(2\/3)=2*(3)/(2)=3](https://img.qammunity.org/2023/formulas/mathematics/college/wxtcyc55nwziet7m5our6l4debk1gpwpqi.png)
![(6)/(2)=3](https://img.qammunity.org/2023/formulas/mathematics/high-school/5xa1z4idz2kz1ew9d85dzxrsmgu1vgpr1p.png)
We get the ratio of the first difference is constant so the given function is an exponential function.
Final answer:
![An\text{ exponential function}](https://img.qammunity.org/2023/formulas/mathematics/college/x8z9zfokbltx3xps1myc2y2n3mmd5wn0cr.png)